The big shift in IT leadership : how great CIOs leverage the power of technology for strategic business growth in the customer-centric economy - Muller, Hunter, 1960- (Hoboken, New Jersey : Wiley, 2015)
'Learn the unique leadership strategies of the effective, essential CIO Beyond the Cloud provides a blueprint for leadership in an era of high volatility, rapid transformation, and amazing growth. An effective CIO is essential to the successful navigation of turbulent and uncertain times, and this insightful guide gives you the actionable framework you need to execute the leadership strategies that work. Focused on the major factors that are critical to modern global enterprise, this book delves into communication, collaboration, relationships, technology, innovation, talent management, and more to provide well-rounded guidance toward principled leadership. Simple, straightforward language explains the basics of each area, and is expanded upon by real-world stories and revealing anecdotes gathered from the author's exclusive interviews with visionary thought leaders from major organizations worldwide. You get perspective from the top on established and emerging leadership strategies, helping you put these ideas to work right away. CIOs are perfectly positioned to provide the leadership required to stay ahead of the competition in complex, rapidly shifting markets. They break down walls, align resources, and facilitate collaboration to drive business value and spur growth amidst an atmosphere of hyper-competition. This guide is your practical handbook for becoming the leader that you need to be. Establish trust and cooperation across the enterprise Recruit and retain the top talent in your field Leverage new technology for continuous business growth Inspire loyalty and optimal performance from everyone on the team The CIO has never been more crucial to the enterprise than right now. With clear guidance toward the unique leadership skills the role requires, Beyond the Cloud is the foundational executive guide for transformational leaders in the new business era'--
Includes index.
Keywords: Information technology -- Management; Strategic planning